2015
DOI: 10.1016/j.taap.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1b1 in polycyclic aromatic hydrocarbon (PAH)-induced skin carcinogenesis: Tumorigenicity of individual PAHs and coal-tar extract, DNA adduction and expression of select genes in the Cyp1b1 knockout mouse

Abstract: FVB/N mice wild-type, heterozygous or null for Cyp 1b1 were used in a two-stage skin tumor study comparing PAH, benzo[a]pyrene (BaP), dibenzo[def,p]chrysene (DBC), and coal tar extract (CTE, SRM 1597a). Following 20 weeks of promotion with TPA the Cyp 1b1 null mice, initiated with DBC, exhibited reductions in incidence, multiplicity, and progression. None of these effects were observed with BaP or CTE. The mechanism of Cyp 1b1-dependent alteration of DBC skin carcinogenesis was further investigated by determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 68 publications
(96 reference statements)
0
17
0
Order By: Relevance
“…On contact with body tissues, they undergo metabolic activation to reactive epoxide compounds through an enzymatic oxidation pathway initiated by cytochrome P450 (CYP), and the formed reactive metabolites are capable of binding to nucleotides on a cellular DNA, forming PAH-DNA adducts. If not repaired, these adducts may induce mutations in oncogenes and suppression genes, eventually leading to the transformation of a normal cell into a cancer cell [3][4][5]. In vivo studies with mice demonstrated mutagenicity of PAHs; for example, pregnant mice exposed to benzo(a)pyrene (B [a]p) for 10 days showed the effects of birth defects [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On contact with body tissues, they undergo metabolic activation to reactive epoxide compounds through an enzymatic oxidation pathway initiated by cytochrome P450 (CYP), and the formed reactive metabolites are capable of binding to nucleotides on a cellular DNA, forming PAH-DNA adducts. If not repaired, these adducts may induce mutations in oncogenes and suppression genes, eventually leading to the transformation of a normal cell into a cancer cell [3][4][5]. In vivo studies with mice demonstrated mutagenicity of PAHs; for example, pregnant mice exposed to benzo(a)pyrene (B [a]p) for 10 days showed the effects of birth defects [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These cell lines express Cyp1a1 protein at significant levels, but not Cyp1b1 protein, indicating that Cyp1b1 has a major role in activating 7,12-DMBA in vivo (32). The Cyp1b1-null mice have also been reported to be reduced in formation of ovarian cancers at a low dose of 7,12-DMBA (33), ovarian and skin tumors caused by DB[a,l]P (34,35), and skin tumors by dibenzo[def,p]chrysene (DB[a,l]P) (36). Disruption of Cyp1b1-null mice has been shown to be reduced in pre-B cell apoptosis (37), bone marrow cytotoxicity (38), and spleen cell immunotoxicity (39) by treatment with 7,12-DMBA.…”
Section: T Shimadamentioning
confidence: 99%
“…Maurya et al reported that polymorphisms of drug metabolizing CYPs showed modest associations with head and neck squamous cell carcinoma risk . Genetic polymorphisms have been reported for CYPs involved in the metabolic activation of polycyclic aromatic hydrocarbons (PAHs) and tobacco‐specific nitrosamines, both of which are wide spreading environmental procarcinogens that induce LC and skin carcinoma . However, Kiyohara C et al have found no significant association between the genetic polymorphism of enzymes involved in xenobiotic metabolism and the risk of LC …”
Section: Introductionmentioning
confidence: 99%
“…17 Genetic polymorphisms have been reported for CYPs involved in the metabolic activation of polycyclic aromatic hydrocarbons (PAHs) and tobaccospecific nitrosamines, 18,19 both of which are wide spreading environmental procarcinogens that induce LC and skin carcinoma. [20][21][22] However, Kiyohara C et al have found no significant association between the genetic polymorphism of enzymes involved in xenobiotic metabolism and the risk of LC. 23 To sum up, the correlation of CYPs polymorphisms and LC risk is contradictory and inconclusive due to the diversity of ethnicity and sample size in study groups.…”
Section: Introductionmentioning
confidence: 99%